COMPARATIVE ANALYSIS OF ROBOTIC, LAPAROSCOPIC, AND OPEN SURGERY: CLINICAL OUTCOMES, COSTS, AND ERGONOMICS - Marianna Rudzińska; Mikołaj Zalewski; Konrad Zieliński; Stanisław Jurkowski; Łukasz Krzystek; Karolina Buć; Paweł Buć; Michał Mazurek; Karolina Ganczar; Jagoda Józefczyk (International Journal of Innovative Technologies in Social Science, 2025)
Background: The evolution of surgical practice has seen a significant shift from open surgery toward minimally invasive techniques. Conventional Laparoscopic Surgery (CLS) replaced many open procedures. It offers benefits like reduced length of hospital stay and lower infection rates. Subsequent technological advancement introduced Robot-Assisted Surgery (RAS), notably utilizing systems like Da Vinci. RAS was specifically developed to overcome the inherent technical limitations of CLS. These include restricted instrument range and two-dimensional viewing. The continuous integration of advanced technologies, including Artificial Intelligence (AI) and Machine Learning (ML), is defining the future role of technology in surgery. This moves towards enhanced precision and autonomous systems. Objective: This analysis aims to synthesize the current evidence comparing Robot-Assisted Surgery (RAS) to Conventional Laparoscopic Surgery (CLS) and open surgery. It focuses on key parameters including clinical outcomes (safety and efficacy), socio-economic costs, and surgeon ergonomics. Methods: This is a narrative synthesis drawing upon recent systematic reviews, meta-analyses, and comparative retrospective studies found in the literature. These primarily compared RAS and CLS across various surgical disciplines. Examples include colorectal surgery, gynecological surgery (e.g., hysterectomy), and nephrectomy. Results: RAS systems offer inherent technical advantages such as superior visualization (3D, high-definition) and enhanced precision due to tremor filtration, motion scaling, and articulated instruments. The learning curve for performing complex technical tasks, such as intracorporeal suturing, is significantly shorter for novice surgeons utilizing robotic assistance compared to those performing CLS. In clinical practice, RAS generally yields comparable results to CLS in terms of major postoperative complications, mortality, and readmission rates. However, RAS is consistently associated with a significantly lower conversion rate to open surgery and a shorter length of hospital stay across nearly all analyzed surgical categories. Conversely, RAS procedures are typically associated with significantly higher total costs (including hospitalization and operative costs) compared to CLS. Furthermore, the operative time for RAS is generally longer than for CLS. In terms of ergonomics, studies indicate that RAS offers better outcomes for surgeons. This results in reduced physical demand and muscle strain compared to the conventional laparoscopic technique. Conclusion: Robotic surgery shows considerable potential for the future, especially for complex surgical procedures performed in anatomically challenging areas. This is primarily due to its ability to minimize conversion rates and shorten hospital stays. Nonetheless, given the substantial associated costs, cost optimization and reduction in equipment and procedure expenses are critical steps. These are required to ensure widespread accessibility and justify its overall value compared to the cost-effective laparoscopic approach.